2008
DOI: 10.1080/02687030601040861
|View full text |Cite
|
Sign up to set email alerts
|

Activation and maintenance of peripheral semantic features of unambiguous words after right hemisphere brain damage in adults

Abstract: Background-The right cerebral hemisphere (RH) sustains activation of subordinate, secondary, less common, and/or distantly related meanings of words. Much of the pertinent data come from studies of homonyms, but some evidence also suggests that the RH has a unique maintenance function in relation to unambiguous nouns. In a divided visual field priming study, Atchley, Burgess, and Keeney (1999) reported that only left visual field/RH presentation yielded evidence of continuing activation of peripheral semantic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…It has been proposed that adults with RHD have a specific deficit in processing metaphors and other non-literal language (e.g., Klepousniotou & Baum, 2005; Lundgren, Brownell, Cayer-Meade, Milione & Kearns, 2011). However, in line with several theories on the continuity of literal and nonliteral language processing (Coulson & Van Petten, 2002; Grady, Oakley & Coulson, 1999; Pynte, Besson, Robichon & Poli, 1996), it is also possible that difficulties with the activation and maintenance of metaphoric meanings reflect a special case of coarse coding in which the non-literal meanings reflect subordinate or distant meanings (Tompkins, Fassbinder et al, 2008; Tompkins, Scharp et al, 2008). In this case, improving the coarse coding process should facilitate access to metaphoric meanings, and improve interpretation of metaphors and perhaps other non-literal language forms.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…It has been proposed that adults with RHD have a specific deficit in processing metaphors and other non-literal language (e.g., Klepousniotou & Baum, 2005; Lundgren, Brownell, Cayer-Meade, Milione & Kearns, 2011). However, in line with several theories on the continuity of literal and nonliteral language processing (Coulson & Van Petten, 2002; Grady, Oakley & Coulson, 1999; Pynte, Besson, Robichon & Poli, 1996), it is also possible that difficulties with the activation and maintenance of metaphoric meanings reflect a special case of coarse coding in which the non-literal meanings reflect subordinate or distant meanings (Tompkins, Fassbinder et al, 2008; Tompkins, Scharp et al, 2008). In this case, improving the coarse coding process should facilitate access to metaphoric meanings, and improve interpretation of metaphors and perhaps other non-literal language forms.…”
mentioning
confidence: 76%
“…Additionally, most studies focus on generation of multiple meanings of homonyms (e.g., Burgess & Simpson, 1988; Klepousniotou & Baum, 2005). Tompkins and colleagues (Tompkins, Fassbinder, Scharp & Meigh, 2008; Tompkins, Scharp, Meigh & Fassbinder, 2008) conducted two direct studies of coarse coding in adults with RHD focusing on activation of distantly-related, or peripheral, features of unambiguous words. To maximize the likelihood that coarse coding processes were being tapped, extensive piloting was conducted to verify that the features were only peripherally related.…”
mentioning
confidence: 99%
“…A large amount of evidence in the literature (see Tompkins, Fassbinder, Scharp, & Meigh, 2008, for a review) supports this suggestion that the processing mechanisms used by the RH maintain activation of the contextual information, particularly peripheral features or subordinate meanings, whereas the LH does not. For example, Faust, Barak, and Chiarello (2006) investigated whether the two hemispheres maintain activation of script meaning (i.e., context) across neutral and unrelated information.…”
mentioning
confidence: 71%
“…Although this sort of finding has been observed in a number of studies investigating particular capacities such as inference generation (Beeman et al, 2000;Mason & Just, 2004) and information maintenance (Tompkins et al, 2008), few behavioural studies have, until recently, demonstrated this advantage for extracting meaning from short contextual sentences. This finding therefore adds to the growing body of evidence that a special contribution of the RH to language tasks is its ability to extract, build and maintain access to a contextual base.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation